ASSESSING THE MANAGEMENT INVOLVEMENT IN SAFETY ISSUES: THE CASE OF METAL PRODUCTS INDUSTRY IN IRAN - Maryam Ooshaksaraie; Mohammad Reza Azadehdel (Asian Academy of Management Journal, 2013)
The concept of management involvement in safety refers to the extent that top and middle level managers get personally involved in critical safety activities within the organisation. Occupational accidents and incidents are symptoms of low management involvement in safety issues, as most of the accidents could be prevented. The main objectives of this study were to evaluate the management involvement in safety issues (like safety values, occupational safety management, and employee well-being), and to analyze the difference in management involvement in the metal products industry in Guilan Province, Iran with regard to company size. A total of 714 respondents from 14 companies participated in the survey. The results showed that management involvement in safety was not strong in the metal products industry in Guilan Province. One-way ANOVA analysis was applied to understand employees’ perspectives on management involvement in safety. The results revealed that there was a significant difference among management involvement in safety with respect to company size. Large companies had stronger management involvement in safety compared to smaller ones.